Viver e morrer nas ruas: um estudo sobre meninos e meninas de rua do Rio de Janeiro - Oliveira, Eliana Rocha (1993)
This is a study on how boys and girls live and die on the streets of the city of Rio de Janeiro, Brazil. The research was made with about seventy children and teenagers that formed two distinct groups. Its main purpose was to get a clear and comprehensive picture of the life and the worldview of this marginalized social group whose basic frames of reference are composed of misery,social adversity, and excludence. To elaborate this picture and to make sense of it the study discussed several theories of marginality. the legal system involved, and the classical solutions that are repeatedly proposed by the society in general such as internment in total institutions. precarious schooling and underemployment. In view of the failure of these solutions it is asked: what are the reasons and motivations for insisting on them? The study concludes that there is a generalized violence praticed upon this young and helpless population group. the so-called street kids: a police and para-military violence: an economic violence, made obvious by the utter impossibility of access to material and cultural goods available to Brazilian society in general: and the pervasi violence which comes from an authoritarian discriminating, and segregationist ideology that excludes these youngsters from their minimal rights as human beings. This study is pervaded by the intention to contribute to the consolidation of a theoretical view engaged with the ideal of social change social justice and the construction of a plural society in which the majority of the Brazilian population - those that do not belong to the economically and culturally hegemoneous classes - will have their places and the chance to express themselves freely and creatively.